Simplification
1. Simplify the Boolean expression
XY′Z′+XY′Z′W+XZ′
The above expression can be written as
XY′Z′ (1+W) +XZ′
=XY′Z′+XZ′ as 1+W=1
=XZ′ (Y′+1)
=XZ′ as Y′+1=1
2. Simplify the Boolean expression
X+X′Y+Y′+(X+Y′) X′Y
The above expression can be written as
X+X′Y+Y′+XX′Y+Y′X′Y
=X+X′Y+Y′ as XX′=0, and YY′=0
=X+Y+Y′ as X+X′Y=X+Y
=X+1 as Y+Y′=1
=1 as X + 1=1
3. Simplify the Boolean expression
Z(Y+Z) (X+Y+Z)
the above expression can be written as
(ZY+ZZ)(X+Y+Z)
= (ZY+Z) (X+Y+Z) as ZZ=Z
=Z(X+Y+Z) as Z+ZY=Z
=ZX+ZY+ZZ
=ZX+ZY+Z as ZZ=Z,
=ZX+Z as Z+ZY=Z
=Z as Z+ZX=Z
4. Simplify the Boolean expression
(X+Y)(X′+Z)(Y+Z)
The above expression can be written as
(XX′+XZ+YX′+YZ)(Y+Z)
=(XZ+YX′+YZ) (Y+Z) as XX′=0
=XZY+YYX′+YYZ+XZZ+YX′Z+YZZ
=XZY+YX′+YZ+XZ+YX′Z+YZ as YY=Y, ZZ=Z
Rearranging the terms we get
XZY+XZ+YX′+YX′Z+YZ as YZ+YZ=YZ
=XZ(Y+1) +YX′+YZ (X′+1) as Y+1=1, X′+1=1
=XZ+YX′+YZ
Now it seems that it cannot be reduced further. But apply the following trick:
The above expression can be written as
XZ+YX′+YZ(X+X′) as X+X′=1
=XZ+YX′+YZX+YZX′
Rearranging the terms we get
XZ+YXZ+Y X′+YX′Z
=XZ (1+Y) +YX′ (1+Z)
=XZ+YX′ as 1+Y=1, 1+Z=1
1. Simplify the Boolean expression
XY′Z′+XY′Z′W+XZ′
The above expression can be written as
XY′Z′ (1+W) +XZ′
=XY′Z′+XZ′ as 1+W=1
=XZ′ (Y′+1)
=XZ′ as Y′+1=1
2. Simplify the Boolean expression
X+X′Y+Y′+(X+Y′) X′Y
The above expression can be written as
X+X′Y+Y′+XX′Y+Y′X′Y
=X+X′Y+Y′ as XX′=0, and YY′=0
=X+Y+Y′ as X+X′Y=X+Y
=X+1 as Y+Y′=1
=1 as X + 1=1
3. Simplify the Boolean expression
Z(Y+Z) (X+Y+Z)
the above expression can be written as
(ZY+ZZ)(X+Y+Z)
= (ZY+Z) (X+Y+Z) as ZZ=Z
=Z(X+Y+Z) as Z+ZY=Z
=ZX+ZY+ZZ
=ZX+ZY+Z as ZZ=Z,
=ZX+Z as Z+ZY=Z
=Z as Z+ZX=Z
4. Simplify the Boolean expression
(X+Y)(X′+Z)(Y+Z)
The above expression can be written as
(XX′+XZ+YX′+YZ)(Y+Z)
=(XZ+YX′+YZ) (Y+Z) as XX′=0
=XZY+YYX′+YYZ+XZZ+YX′Z+YZZ
=XZY+YX′+YZ+XZ+YX′Z+YZ as YY=Y, ZZ=Z
Rearranging the terms we get
XZY+XZ+YX′+YX′Z+YZ as YZ+YZ=YZ
=XZ(Y+1) +YX′+YZ (X′+1) as Y+1=1, X′+1=1
=XZ+YX′+YZ
Now it seems that it cannot be reduced further. But apply the following trick:
The above expression can be written as
XZ+YX′+YZ(X+X′) as X+X′=1
=XZ+YX′+YZX+YZX′
Rearranging the terms we get
XZ+YXZ+Y X′+YX′Z
=XZ (1+Y) +YX′ (1+Z)
=XZ+YX′ as 1+Y=1, 1+Z=1
0 comments:
Post a Comment